Um programa de auto-educação para professores de português como segunda língua - Araújo, José Paulo de (1995)
Investigates a proposal for the self-education of teachers of Portuguese as a Second/Foreign Language (PSL/PFL), which is based on Widdowson's (1990) model (a Pramatics of Language Teaching). By using a syllabus developed in accordance with this theoretical model. I carried out an ethnographic investigation on the practices and beliefs of a beginner PSL teacher. The results obtained indicate that the education of PVL/PFL teachers could not consist only of readings of theoretical subjects and of tasks or suggestions for classroorn research. Data indicate that the process of teacher education should include a process of self-reflection, which would make it possible for teachers to evaluate both major theoretical paradigms and whatever theoretical knowledge produced by themselves. This could contribute to the development of these teacher’s critical thinking and autonomy.